Low‐Temperature Topochemical Transformation of Bi13Pt3I7 into the New Layered Honeycomb Metal Bi12Pt3I5. Issue 51 (28th October 2014) - Kaiser, Martin; Rasche, Bertold; Isaeva, Anna; Ruck, Michael
Abstract Ordered single‐crystals of the metallic subiodide Bi13Pt3I7 were grown and treated with n‐butyllithium. At 45 °C, complete pseudomorphosis to Bi12Pt3I5 was achieved within two days. The new compound is air‐stable and contains the same <alternatives> <![CDATA[${{{\hfill 2\atop \hfill \infty }}}$]]> <inline-graphic xlink:href="ark:/27927/pgh2qsv59jk" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>[(PtBi8/2)3I]n+ honeycomb nets and iodide layers as the starting material Bi13Pt3I7, but does not include <alternatives> <![CDATA[${{{\hfill 1\atop \hfill \infty }}}$]]> <inline-graphic xlink:href="ark:/27927/pgh2qsv59k4" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>[BiI2I4/2]− iodidobismuthate strands. Electron microscopy and X‐ray diffraction studies of solid intermediates visualize the process of the topochemical crystal‐to‐crystal transformation. In the electronic band structures of Bi13Pt3I7 and Bi12Pt3I5, the vicinities of the Fermi levels are dominated by the intermetallic fragments. Upon the transformation of Bi13Pt3I7 into Bi12Pt3I5, the intermetallic part is oxidized and the Fermi level is lowered by 0.16 eV. Whereas in Bi13Pt3I7 the intermetallic layers do not interact across the iodidobismuthate spacers (two‐dimensional metal), they couple in Bi12Pt3I5 and form a three‐dimensional metal.